Analisis Kinerja Virtual Router Redudancy Protocol (VRRP) Di Mikrotik Router Pada Dirjen Sumber Daya Air Balai Besar Wilayah Sungai Sumatera VIII - Alhimni Alhimni; Ilman Zuhri Yadi (Jurnal Pengembangan Sistem Informasi dan Informatika, 2020)
This research is based on the observations and experiences of researchers, that now the internet has become a basic need for an agency, almost all Directorates of Water Resources (SDA) have a computer network. The Directorate of Water Resources (SDA) Central Sumatra River Basin VIII has implemented a network to support the performance of the Directorate of Water Resources (SDA), but still has problems where the network often experiences disconnections due to damage, interference with switches, damage to cables and network connectors. and Hang routers. To meet the internet needs at the Directorate of Water Resources (SDA) Central Sumatra VIII River Basin, stable internet is needed, therefore a failover method is needed. The problem in this research is that there are frequent disturbances in the internet network. The transfer of the main internet line to the backup path is done manually. Given how important the network is to support performance at the Directorate of Water Resources (SDA), the authors suggest to create a failover backup system for Mikrotik routers in the Directorate of Water Resources (SDA). This research uses the Action Research development method, which consists of Diagnostic, Action planning, action taking, evaluating and e-learning. With this application, it is hoped that if there is a problem with the router device, it will not interfere with the use of the existing network. On the internet network of the Directorate of Water Resources (SDA) Central Sumatra River Region VIII.